The Predictors Of Typing Performance In Office Employees With Neck Pain; Neck Disability, Muscle Activity, Posture, And Demographics - KESKİN DİLBAY, NİLÜFER (My University, 2022)
Introduction: It is important to determine the predictors affecting performance to protect the professional performance and increase productivity. In the present study, the purpose was to show the relations between typing performance and neck disability, Upper Trapezius (UT) muscle activation, posture, and demographic characteristics in office employees who have neck pain. Methods: The demographic data were obtained from 21 office employees (10 women, 11 men) who used computers for at least 4 hours a day, and neck pain-related disability levels were determined with the Neck Disability Index (NDI). The participants were given a 10-minute typing task in their working environments, during which right and left UT muscle activation was recorded with Surface Electromyography (sEMG). Work posture was evaluated with Rapid Upper Limb Assessment (RULA) and Forward Head Posture (FHP) was evaluated with Cervical Range of Motion (CROM) Device. Results: Right and left UT muscle activation was found to be higher in women. NDI and right UT muscle activation were correlated positively. Typing performance was correlated positively with work-hour, and negatively with age, job experience, and RULA-Score. The hierarchical regression analysis showed that right UT muscle activation, RULA score, age, and body mass index may be among the predictors of typing performance. Conclusion: To maintain and improve the current performance, approaches must be determined for employees and workplaces, considering variables such as muscle activation, working posture, age, and body mass index.
Keywords: Office employees; neck pain; typing performance; muscle activity; posture